Provider costs of Antiretroviral therapy (ART) in Zimbabwe: The value of using time-driven activity based costing methods in a low resource setting - Juliet Gamuchirai Nyamasve; Carren Pindiriri; Tonderai Mapako; Alex Ingwani; Shevone Corbin; Owen Mugurungi; Tsitsi Apollo; Shepherd Chikomo; Kundai Chikambure; Shepherd Shamu; Linden Morrison; Nokuthula Mujuru; et al. (PLoS ONE, 2026)
Although ART has transformed HIV into a manageable chronic condition, significant cost and logistical challenges persist, threatening progress toward the UNAIDS 95-95-95 targets. Budget allocation to the health sector declined by over 30% in the last decade in Zimbabwe, attributed to donor fatigue and emergence of pandemics. The time-driven activity-based costing (TDABC) method was used to estimate the provider costs of ART and inform resource allocation for sustained ART programming. A descriptive cross-sectional study in 11 facilities across Zimbabwe’s four levels of care collected data using standardized instruments, capturing over 2,500 provider-recipient observations. Process maps of HIV care pathways were developed with subject matter experts to document resource use and standard of care. Time taken to deliver ART services, cost of space and cost of equipment were used to calculate costs and validated by national level stakeholders. In 2022, annual provider costs for ART in totalled $168.66 million for 1.2 million patients. National costs are projected to $192.44 million by 2026, attributed to declining HIV-related mortality and incidence. Primary care facilities bore 75% of costs due to higher patient volume. Provider costs averaged $57.05 for adult ART initiation and $62.70 for paediatric initiation. First-year ART costs per client were $252.78 (adult) and $450.56 (paediatric). Annual maintenance costs were $138.93 for first-line and $174.93 for second-line ART. Laboratory services ($30.72) contributed more to adult ART costs than medicines ($27.98). ART costs exceeded prior estimates, driven by facility-level differences, laboratory expenses, and paediatric formulations. Task-shifting proved cost-efficient, but sustainability is threatened by funding gaps and low health worker compensation. Optimizing laboratory systems and decentralizing services remain critical. External funding withdrawal created an annual gap of more than $50 million. Sustaining ART to 2030, requires improving domestic resource mobilization, strengthening ART decentralization, and designing cost-efficient laboratory models that preserve treatment quality.